2018
DOI: 10.3389/fneur.2018.00207
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-National Institute of Neurology and Neurosurgery-Stroke Registry: Results of a 25-Year Hospital-Based Study

Abstract: Background and purposeStroke has been scarcely studied in Latin America (LA). The Mexican Institute of Neurology Stroke Registry was established in 1990 as a prospective computer-based database to register data obtained from patients admitted with stroke. Using this data, we attempted to define the profile of risk factors and outcomes.MethodsThe demographic data, stroke description, ancillary tests, vascular risk factors, and modified Rankin scale (mRs) were registered. Ischemic stroke subtyping was based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
5
0
10
Order By: Relevance
“…Conventional craniotomy for hematoma removal plus bone flap decompression is commonly used for patients with large volume hematoma. Previous studies demonstrated that it could reduce the intracranial pressure, prevent and reduce blood cell decomposition after bleeding, increase the survival rate, and improve the quality of life [ 29 , 30 ]. However, iatrogenic injuries of conventional open surgery remain serious.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional craniotomy for hematoma removal plus bone flap decompression is commonly used for patients with large volume hematoma. Previous studies demonstrated that it could reduce the intracranial pressure, prevent and reduce blood cell decomposition after bleeding, increase the survival rate, and improve the quality of life [ 29 , 30 ]. However, iatrogenic injuries of conventional open surgery remain serious.…”
Section: Discussionmentioning
confidence: 99%
“…In a large stroke registry in our hospital, approximately 6.3% of all stroke patients during a 25-year period were CVT cases. Many of these patients developed severe presentations with bilateral infarcts (27.9%) and haemorrhagic transformation (38.4%) [ 2 ] . In our patient, a diagnosis of malignant CVT was made because of her rapid neurological deterioration, bilateral venous infarcts, haemorrhagic transformation and severe oedema with bilateral midline shift.…”
Section: Discussionmentioning
confidence: 99%
“…Se encontró que la EVC se presenta en edades más tempranas en comparación con registros anteriores, los niveles de hipertensión van en descenso, hay mayor proporción de trombosis venosa profunda y altos niveles de dependencia funcional -según escalas de actividades instrumentales de la vida diaria (AIVD)-. Sin embargo, el estudio no va más allá del perfil de factores de riesgo, sin establecer recomendaciones para las políticas de salud pública 10 . Figura 1.…”
Section: Metodologíaunclassified